Parental and emerging adult psychopathology: Moderated mediation by gender and affect toward parents. (October 2015) - Walker, Courtney S.; McKinney, Cliff
Abstract: Current research indicates that children tend to view parents with psychopathology more negatively and children who hold negative perceptions of parents are at a greater risk for psychopathology. Yet, less research examines how parental psychopathology influences offspring psychopathology through affect toward parents. The current study tested a model that examined the associations among parental psychopathology, positive affect toward parents, and emerging adult psychopathology. Associations were expected to be partly indirect via positive affect toward parents and emerging adult gender was expected to moderate these associations. Results indicated gender-moderated mediation with significant effects found for males but not females. Results from the current study emphasize the importance of examining affect toward parents as a risk factor for emerging adult psychopathology. Additionally, results of the current study demonstrate the importance of examining the role of emerging adult gender as a potential moderator in these relationships.